REPORT: Proposed upgrading of Teluk Batik Resort for Pangkor Discovery & Outdoor Quest Sdn Bhd at Teluk Batik Resort, Jalan Teluk Batik, 32200 Lumut, Perak / Nur Syamimi Bakri - Bakri, Nur Syamimi (Faculty of Architecture, Planning and Surveying, 2011)
This Diploma level Interior Design final project is towards student understanding about the interior design project’s whole aspect that had been studied from the basic level until the design proposal presentation. The selected final project is a proposed upgrading of Teluk Batik Resort for Pangkor Discovery and Outdoor Quest Sdn Bhd at Teluk Batik Resort, Jalan Teluk Batik, 32200, Lumut, Perak. This proposed restaurant is to attract many tourists, especially from the other country. Concept and image that had been chosen not only must suitable with the clients as both of it would reflect the client itself, but at the same time it would give a positive impact and to increase the business in the resort. Besides, the concept and image itself should be also related with the theme of the resort. Some of the gained information of the study is through interviews, printed media, internet, observation, and through the result from the case Study either locally or internationally.